CuddleCraft Co. / Asma Salsabila Azaili … [et al.]. - Azaili, Asma Salsabila; Mohd Salleh, Nor Anisah; Razali, Nur Ismah; Maszeli, Nur Maizatul Nabila; Mohd Razali, Siti Khairunissa
CuddleCraft Co., located in Seksyen 13, Shah Alam, stands out for its unique approach to showcasing art through personalized and unique tuft pieces. Positioned strategically amid malls, ensuring high footfall with limited competitors. We cater to a diverse audience including locals, youngsters, tourists, and students. Our store sells various types of products which are based on the tufting process. Customers can choose the design, color, pattern, size, and product that they want to make without worrying about the price because our story provides the most competitive prices in the tufting market. Furthermore, CuddleCraft Co. gives special services to every customer who comes to our store and buys our product. The services include free pictures, customized orders for married couples, tufting for tote bags, and the ability to design one’s own piece. CuddleCraft Co. used social media such as Instagram, Tik Tok, and Facebook for marketing, and collaboration with universities and schools to enhance our brand visibility. Not only that, we even offer free exhibitions, selling ready-made products and providing tufting machine tutorials to engage and educate our customers. Our business is run by five main employees, who hold responsibility as general manager, administrative manager, marketing manager, operational manager, and financial manager. All of us have a responsibility to make sure the vision and mission of our business will be achieved. From what we observed, our store needs to keep updated with the market trend to make sure we are not left behind and it will attract customers to come to our store. This is also an initiative for us to gain more sales and open another branch of CuddleCraft Co. in another state. Our goal in the future is to export our business internationally through online platforms. Lastly, we are confident that our business will grow successfully as tufting products are one of the best-trending things nowadays and we will grab a great opportunity in making this business happened.